Penilaian Persediaan Barang Dagang Berdasarkan SAK EMKM pada BUMDES Karya Maju Kecamatan Keluang Kabupaten Musi Banyuasin - Eka Sevtia Mesta; Ryan Al Rachmat (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The purpose of this study was to determine how the accounting treatment of inventory on the method of recording and assessing merchandise at Bumdes Karya Maju Kec. Kab. Musi Banyuasin with inventory observation periods in April and May 2020. In this study the researchers used a qualitative descriptive analysis method. The types of data used are primary and secondary. Where the primary data is in the form of interviews and field observations, while the secondary data is in the form of merchandise inventory data at Bumdes Karya Maju. Data collection methods used were interviews and field observations. The results showed that the method of recording and inventory of merchandise at Bumdes Karya Maju was not in accordance with SAK EMKM. Bumdes Karya Maju records merchandise inventory using an application called OMI, which has not applied any method in the application.